Implementation of a “Mortgage Smart Pricing Engine” based on advanced analytics solutions - Internship at Millennium BCP - Pereira, Bernardo Gamito (2021)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics